METHODS COMPARISON OF ARAS AND TOPSIS FOR DETERMINING THE BEST PRACTICUM ASSISTANT (CASE STUDY CHEMICAL LABORATORY DEPARTMENT OF FMIPA UHO) - Statiswaty; Ayu Pratiwi; Natalis Ransi (Fakultas Teknik Universitas Lambung Mangkurat, 2022)
Practicum is one of the activities that are part of the curriculum in universities. The role of a practicum assistant is needed to support practicum activities. Practicum assistants is a selected through a selection process. The selection of practicum assistants at the Faculty of Mathematics dan Natural Science (FMIPA), Halu Oleo University, to be precise the department of Chemistry, is still done through a manual process. The problem faced in the selection process is that each lecturer determines the ranks of the selected practicum assistants sequentially, from the first practicum supervisor lecturer to the last, which takes a long time and subjective assessment is unavoidable. Then from that problem, it is necessary to develop a computerized system as a supporting media in decision-making to facilitate selecting practicum assistants. The Additive Ratio Assessment (ARAS) and Technique For Others Reference By Similarity To Ideal Solution (TOPSIS) method applicated to compare the results of the two ways. The results of the comparison of the two methods show that TOPSIS provides a higher accuracy value of 50%, while the accuracy value of the ARAS method is 44%, but from testing the speed of processing data, the ARAS method is faster than the TOPSIS method.